THE EFFECTIVENESS OF THE FLIPPED CLASSROOM ON STUDENTS LEARNING INDEPENDENCE IN AQIDAH AND AKHLAK - Ningrum Ningrum; Heru Juabdin Sada; Erni Yusnita (Program Studi Pendidikan Agama Islam, 2026)
This study investigates the effectiveness of the flipped classroom model in enhancing students’ learner autonomy in Akidah Akhlak at MAN 2 Bandar Lampung, with particular attention to low levels of initiative and creativity. A quantitative experimental method with a posttest-only control group design was employed. The sample was selected through simple random sampling, designating class XI Science 4 as the control group (conventional learning) and class XI Science 5 as the experimental group (flipped classroom). The instrument used was a learner autonomy questionnaire consisting of 15 valid and reliable items. Data analysis included prerequisite tests (normality and homogeneity) and a pooled variance t-test. The results revealed a significant difference between the two groups. Students in the flipped classroom exhibited higher autonomy, initiative, and creativity compared to those in conventional settings. These findings are consistent with constructivist theory, which emphasizes active and participatory learning, and demonstrate that the flipped classroom can be effectively adapted to value- and spirituality-based subjects. The novelty of this research lies in its application of the flipped classroom to Akidah Akhlak, a subject rarely examined in this context, thereby expanding the model’s effectiveness beyond the natural and social sciences. The study implies that the flipped classroom may serve as an alternative strategy for teachers to foster learner autonomy while simultaneously strengthening students’ character.